Application of a team integration performance index in road infrastructure alliance projects. Issue 5 (4th July 2016) - Che Ibrahim, Che Khairil Izam; Costello, Seosamh B.; Wilkinson, Suzanne
Abstract : Purpose: – The purpose of this paper is to explore the applicability of the Alliance Team Integration Performance Index (ATIPI) model as an assessment tool to measure the performance of team integration in alliance road infrastructure projects in New Zealand. Design/methodology/approach: – This study takes a case study approach, using a qualitative research method. Three road infrastructure projects under project alliance from the New Zealand Transport Agency (NZTA) were selected as the cases. Data were collected through the interviews with a representative from the alliance management team from each case. Project records and documentation were also used to assist and support the actual data from the interviews. Findings: – The findings indicated that the ATIPI is performing as expected and found to be both practical and applicable to measure the team integration performance in light of real life case studies of alliance road infrastructure projects. Across the three case studies, there is evidence that high levels of integrated performance is consistently fostered by the project teams over the lifecycle of projects. In addition, based on the cross-case analysis from the application of the ATIPI on three cases, further work could enhance the probability of the utilization of the tool to manage different project alliance teams consistently and objectively. Research limitations/implications: – The study was limited to three alliance road infrastructure projects in New Zealand. Further research into different alliance projects is required to establish a comprehensive database of alliance team integration performance, so that the model could be more beneficial for owner and non-owner participants, for benchmarking purposes. Practical implications: – As team integration practice can directly result in high performing teams in alliance projects, the ATIPI is an ideal model to facilitate the continuous evaluation of team integration performance consistently and objectively over the lifecycle of the projects. Originality/value: – This study extends the team integration literature in construction research by providing significant insights into the empirical evaluation of alliance team integration performance, as well as providing added value for the enhancement of any future development of performance evaluation models in construction research.